Mastering your Fellowship: Part 2, 2025 - Mergan Naidoo; Klaus von Pressentin; John M. Musonda; Selvandran Rangiah; Chantelle van der Bijl (South African Family Practice)
The ‘Mastering your Fellowship’ series provides examples of the question format encountered in the written and clinical examinations for the Fellowship of the College of Family Physicians of South Africa (FCFP [SA]) examination. The series is aimed at helping family medicine registrars prepare for this examination.